Short‐term dietary methionine restriction with high fat diet counteracts metabolic dysfunction in male mice - Marissa I. McGilvrey; Bethany Fortier; Diana Cooke; Maryam A. Mahdi; Benjamin Tero; Christian M. Potts; Abigail Kaija; Larisa Ryzhova; Carolina Cora; Adam Richardson; Douglas Guzior; Ilka Pinz; et al. (Physiological Reports, 2025)
Abstract Dietary methionine restriction (MetR) promotes metabolic health, and we tested the impact of short durations of MetR on high fat diet (HFD)‐induced metabolic dysfunction with the maintenance of HFD. Male C57BL/6J mice were fed HFD from 10 to 25 weeks of age, then maintained on HFD or fed HFD with 80% reduced methionine (HFD‐MetR) for 3, 5, or 10 days. Blood, liver, adipose tissue, and aortae underwent phenotypic assessment, proteomics, and metabolomics. HFD‐MetR induced rapid weight loss and robust metabolic improvement within 10 days. Significant reductions in body weight, circulating triglycerides, glucose, insulin, adipokines and hepatokines reflected metabolic health. Proteomics revealed enriched metabolic signatures in perivascular adipose tissue (PVAT) and structural remodeling signatures in aorta. Metabolomics identified a cardioprotective signature in blood plasma, and activated mitochondrial activity and energy production in liver and brown adipose tissue. HFD‐MetR reversed metabolic dysfunction, and novel proteomic and metabolomic signatures were identified. Multi‐organ molecular changes in lipid metabolism, mitochondrial function, and bioenergetics are predicted to impact adipose tissue and liver function and cardiovascular health. Our identification of rapid changes in protein and metabolite signatures with accelerated restoration of metabolic health can be leveraged to evaluate biomarkers of metabolic health and disease in a translational context.